EDUKASI PENYAKIT DBD DAN PENCEGAHANNYA PADA SISWA SDN 39 PASAR AMBACANG DI KECAMATAN KURANJI KOTA PADANG - Yeffi Masnarivan; Arinil Haq; Desmi Dodi Putra; Mirna Saputri (BULETIN ILMIAH NAGARI MEMBANGUN, 2023)
The problem of increasing the incidence of Dengue Hemorrhagic Fever (DHF) is a very important thing to overcome, the implementation of prevention and control is one way out of this problem. Based on the current situation in the field, it seems that there are always cases of DHF in the city of Padang every year, so it still needs to get more attention. For this reason, the education sector needs to support this effort by holding training and forming larva monitoring students (Wamantik) in schools. This activity aims to increase students' knowledge about DHF and prevention efforts, as well as the formation of Wamantik in schools. This activity was carried out at State Elementary School (SDN) 39 Pasar Ambacang, Padang City. The target audience is a representative of elementary school students from grades 3 to grade 6, each of which is 3 people so that the number of participants is 12 people using the educational counseling method and hands-on practice. The results of this activity began with an introduction by the community service team. The next activity is the delivery of materials and training related to DHF, methods of transmission of DHF, symptoms/signs of DHF, help for DHF sufferers, introduction to DHF vectors, and efforts to prevent DHF, as well as the importance of forming a pattern in schools and the form of implementation. Participants were enthusiastic in participating in the activity. From the results of the pretest and post test, it was found that participants' knowledge increased before and after carrying out activities related to DHF and Wamantik. It can be concluded that the education carried out can increase participants' knowledge related to DHF and Wamantik.